History and peasant memory: Silences and representations on peasant struggle for land and repression in Ongoy - Chati, Guido (2015)
This article argues that there are social spaces in Peru where alternative memories about the political violence that took place between 1980 and 2000 are produced. In Andahuaylas, Apurímac, recurrent narratives tell about servitude in the hacienda, peasant mobilization for the restitution of their land, land occupation and its violent repression. A victorious memory of the land occupation exists alongside of an oppressive memory of internal war. Yet these representations have been silenced by official studies on memory, which are now so fashionable.In Ongoy, Andahuaylas, in the guise of a conflict between communities and hacienda, there are peasant’s political practices in relation with respect to the state. Peasants developed association networks with state institutions, trade unions, students, migrants, political parties and others to seek the restitution of their land. They gathered documents which they use in support of their memory and seniority in the territory. These show that the struggle for land that culminated in 1963 with the occupation of land, the slaughter of peasants and repression, has colonial origins. These are stories and memories that reconstruct the land struggle as a heroic act and overlap with other more recent representations of political violence. To analyze the process, events in Ongoy between 1960 and 1969 are reconstructed in dialog with the peasants gathered documents and testimonies of the actors on how events are reinterpreted after political violence.